Hubungan Spiritualitas, Motivasi Kerja dengan Kinerja Guru PAK di Kecamatan Tarutung - Adiankoting Kabupaten Tapanuli Utara - Fanorotodo Laia (Jurnal Teologi Cultivation, 2021)
AbstractThis study aims to determine the relationship between Spirituality and Work Motivation together with the Performance of Christian Religious Education Teachers in Tarutung and Adiankoting Districts, North Tapanuli Regency in 2017. This study uses a descriptive quantitative method approach. The population is all teachers of Christian Religious Education in Tarutung and Adiankoting Districts totaling 31 people as well as being the sample. The research instrument was a closed questionnaire, which was compiled by the researcher based on the indicators of the research variables. The questionnaire test was conducted on 30 respondents who were not the research sample, and had been tested with validity and reliability tests. This research is accepted as true with the data: 1). The X1Y correlation is 0.584 and the coefficient of determination is 34.10%, which shows that 34.10% of teacher performance is determined by teacher spirituality. 2). The X2Y correlation is 0.631 and the coefficient of determination is 39.81%, which shows that 39.81% of teacher performance is determined by work motivation. 3). Double correlation RX1X2Y=0.664 and coefficient of double determination R2 = 44.08%, which means teacher performance of 44.08% is determined by spirituality and work motivation together, partly determined by other factors as well as problem identification. The result is that there is a positive relationship between spirituality and work motivation with the performance of Christian Religious Education teachers in Tarutung and Adiankoting Districts, North Tapanuli Regency in 2017 individually or together because it has been tested empirically. The implication is that if it is to improve performance, teachers must increase their spirituality and work motivation.Keywords : performance; spirituality; work motivation. AbstrakPenelitian ini bertujuan untuk mengetahui hubungan Spiritualitas dan Motivasi Kerja secara bersama-sama dengan Kinerja Guru Pendidikan Agama Kristen di Kecamatan Tarutung dan Adiankoting Kabupaten Tapanuli Utara Tahun 2017. Penelitian ini menggunakan pendekatan metode kuantitatif deskriptif. Populasi adalah seluruh guru Pendidikan Agama Kristen di Kecamatan Tarutung dan Adiankoting berjumlah 31 orang sekaligus menjadi sampel. Instrumen penelitian berupa angket tertutup, yang disusun oleh peneliti berdasarkan indikator variabel penelitian. Uji coba angket dilakukan kepada 30 responden yang bukan sampel penelitian, dan telah teruji dengan uji validitas dan reliabilitas. Penelitian ini diterima kebenarannya dengan data: 1). Korelasi X1Y sebesar 0.584 dan koefisien determinasi sebesar 34.10%., yang menunjukkan bahwa 34.10% kinerja guru ditentukan oleh spiritualitas guru. 2). Korelasi X2Y sebesar 0.631 dan koefisien determinasi sebesar 39.81%, yang menunjukkan bahwa 39.81%  kinerja guru ditentukan oleh  motivasi kerja. 3). Korelasi Ganda RX1X2Y=0.664 dan koefisien determinasi ganda R2 = 44.08%, yang berarti Kinerja guru sebesar 44.08% ditentukan oleh spiritualitas dan motivasi kerja secara bersama-sama, sebahagian lagi ditentukani oleh faktor lain sebagaimana pada identifikasi masalah. Hasilnya adalah  terdapat hubungan yang positif antar spiritualitas dan motivasi kerja dengan kinerja guru Pendidikan Agama Kristen di Kecamatan Tarutung dan Adiankoting Kabupaten Tapanuli Utara Tahun 2017 secara sendiri-sendiri maupun bersama-sama karena telah teruji secara empiris. Implikasinya, jika akan meningkatkan kinerja, guru harus meningkatkan spiritualitas dan motivasi kerjanya. Kata Kunci: kinerja; motivasi kerja; spiritualitas.